PENGARUH PENGELUARAN PEMERINTAH BIDANG PENDIDIKAN DAN KESEHATAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA BARAT TAHUN 2016-2019 - Sasongko , Hendro; Ilmiyono , Agung Fajar; Aldillah, Zhafira Huriya (Jurnal Akunida, 2021)
Economic growth as an increase in community output caused by the increasing number of production processes without any changes in the methods or technology itself. There are four factors of economic growth, namely human resources, natural resources, capital formation, and technology. Government spending acts as capital formation as the provision of public facilities, but without these public facilities the private sector will not want to invest. The purpose of this study was to examine (1) The Effect of Government Spending on Education on Economic Growth in West Java Province (2) The Effect of Government Spending on Health on Economic Growth in West Java Province (3) The Effect of Simultaneous Government Expenditure on Education and Health on Economic Growth in West Java Province. This research was conducted in cities/districts in West Java Province in 2016-2019. The sample used in this study were 11 cities/districts. The sample was selected using purposive sampling method. This type of research is verification using the explanatory survey method, which is the method used to test the hypothesis. The data were tested using Eviews 8 with panel data model selection, classical assumption testing using normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, panel data regression analysis, and hypothesis testing using t test, f test, and R2 test. Partial testing with the t-test shows that government spending on education is positive and has no significant effect on economic growth, this is due to the government's less than optimal effort in absorption budget allocations in West Java Province. Government spending in the health sector has a positive and significant effect on economic growth, so that the government's efforts have been maximized in the absorption of budget allocations in West Java Province. Simultaneous test results with the f test, namely government spending on education and health together have a positive and significant effect on economic growth in West Java Province.